"The effect of R.E.A.C.T strategy on the achievement of fifth-grade students in chemistry" - Yasir, Murtadha Azeez; Hamza, Ghada Sherif Abdel; Issa, Fadel Omran (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to identify the impact of the REACT strategy on the achievement of fifth-grade students for biochemistry, and to verify the goal the researcher set a zero hypothesis that states: There is no statistically significant difference at the level of significance (0.05) between the average scores of students of the experimental group who will study according to the REACT strategy and the average score Students of the control group who will study according to the usual method of testing the achievement of the chemistry subject, and in order to verify it according to his experience in the first semester of the academic year (2019 - 2020), as the research sample consisted of (60) students from the fifth grade of biology students in Al-Khwarizmi’s course For boys, and They were randomly assigned to two groups by (30) students in each group, and the two groups were rewarded in the following variables: chronological age, successful intelligence test, the second course degree from the previous academic year in chemistry, and the testing of previous information, and in light of the relative importance of the content For behavioral purposes, an achievement test consisting of (35) items was constructed, of which (28) were a multiple choice type and (7) paragraphs of the essay questions type, and the researcher has verified the psychological characteristics of the test, the experiment continued to apply (10) weeks, and in At the end of the experiment, the achievement test was applied to the two groups D that analyzed the results and demonstrated the superiority of the experimental group students who studied according to the R.E.A.C.T strategy over the control group who studied in the usual way in the academic achievement variable.